2018
DOI: 10.1371/journal.pone.0200438
|View full text |Cite
|
Sign up to set email alerts
|

Landscape heterogeneity rather than crop diversity mediates bird diversity in agricultural landscapes

Abstract: Crop diversification has been proposed as farm management tool that could mitigate the externalities of conventional farming while reducing productivity-biodiversity trade-offs. Yet evidence for the acclaimed biodiversity benefits of landscape-level crop diversity is ambiguous. Effects may strongly depend on spatial scale and the level of landscape heterogeneity (e.g. overall habitat diversity). At the same time, contrasting within-taxon responses obscure benefits to specific functional groups (i.e. species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 48 publications
6
61
0
Order By: Relevance
“…We found a negative significant correlation between SDI and ESA. Our results confirm that, at the regional (CLC) scale, the increasing landscape heterogeneity has a negative effect on the population of the Eurasian skylark [19,21,37,40,41]. The increasing heterogeneity results in a lower abundance of the Eurasian skylark.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found a negative significant correlation between SDI and ESA. Our results confirm that, at the regional (CLC) scale, the increasing landscape heterogeneity has a negative effect on the population of the Eurasian skylark [19,21,37,40,41]. The increasing heterogeneity results in a lower abundance of the Eurasian skylark.…”
Section: Discussionsupporting
confidence: 82%
“…According to Chamberlain et al (2001) [45], in England, the skylark density increased with habitat heterogeneity; nevertheless, farmland plots in the lowlands of England showed decreased skylark density with increasing habitat heterogeneity. These results suggest that the crop type is more important than the crop heterogeneity value [41]. According to Blaschke et al [46], an increase in cultivation of bioenergy crops inside the biogas energy landscape will decrease the land availability for traditional agriculture and nature conservation.…”
Section: Discussionmentioning
confidence: 97%
“…Agricultural landscapes characterised by large fields and few ecotones possess low compositional and configurational habitat complexity (Robinson and Sutherland ). In such simplified landscapes, abundance and diversity of animals is often reduced (Fahrig et al , Newbold et al , Redlich et al ). A potential underlying mechanism might be that on the landscape scale resource heterogeneity increases with decreasing habitat complexity, making it more difficult for consumers to find food resources (Mueller and Fagan ).…”
Section: Introductionmentioning
confidence: 99%
“…Using data from 31 countries, Karp et al (2018) reported inconsistent associations between pest control and semi-natural habitats in the surrounding landscapes, suggesting that the semi-natural habitats in the agricultural landscape do not always enhance biological control of herbivores. Furthermore, some crops, including alfalfa (Costamagna et al, 2015) and wheat (Samaranayake & Costamagna, 2018), and crop diversity (Redlich et al, 2018) have been associated with increased pest control services, suggesting that crop habitats may also function as temporary sources of natural enemies .…”
Section: Introductionmentioning
confidence: 99%